2017
DOI: 10.2147/ppa.s123294
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on the overuse of blood test-guided antibiotics on patients with acute diarrhea in primary hospitals of China

Abstract: BackgroundOveruse with antibiotics in the treatment of infectious diseases has become a central focus of public health over the years. The aim of this study was to provide an up-to-date evaluation of the blood test-guided antibiotic use on patients with acute diarrhea in primary hospitals of China.Materials and methodsA cross-sectional survey was conducted on 330 patients with acute diarrhea in Shanghai, People’s Republic of China, from March 2013 to February 2016. These patients were treated with or without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…However, it has been suggested by international guidelines that doctors should not perform testing or initiate antibiotic therapy in people with acute bronchitis (pneumonia excluded) 24. Studies25 26 have shown that blood tests do not accurately differentiate between bacterial and viral infections. In our survey, many doctors also reported using raised CRP as a criterion for prescribing antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been suggested by international guidelines that doctors should not perform testing or initiate antibiotic therapy in people with acute bronchitis (pneumonia excluded) 24. Studies25 26 have shown that blood tests do not accurately differentiate between bacterial and viral infections. In our survey, many doctors also reported using raised CRP as a criterion for prescribing antimicrobials.…”
Section: Discussionmentioning
confidence: 99%